Stranger things 4 [compact disc] : soundtrack from the Netflix series. - Bush, Kate; Arnette, Mae; Falco; Nelson, Rick, 1940-1985; Fitzgerald, Ella; Armstrong, Louis, 1901-1971; Derringer, Rick; Taylor, James, 1948-; Moby (Netflix/Legacy, 2022)
Stranger Things season four is scheduled to be released worldwide exclusively via Netflix's streaming service in two volumes. The fourth season will have nine episodes and has continued to be produced by the show's creators the Duffer Brothers, along with Shawn Levy, Dan Cohen, and lain Paterson. The soundtrack will include key music covering various classic eras and styles as featured in season four. The soundtrack album is conceptualized and produced by The Duffer Brothers and Nora Felder. The compilation album is produced by The Duffer Brothers and two-time Grammy nominee Timothy J. Smith.